Penguatan Manajemen Usaha pada UMKM Gethuk Bu Sri: Strengthening Business Management at Gethuk Bu Sri MSMEs - Harisudin, Mohamad; Riptanti, Erlyna Wida; Khomah, Isti; Qonita, Raden Rara Aulia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Community service aims to strengthen business management for Gethuk Bu Sri MSMEs, which produce traditional foods, through targeted training in marketing, basic bookkeeping, and applying Good Manufacturing Practices (GMP). UMKM Gethuk Bu Sri has weak business management problems, including marketing, financial, and production management. This service activity uses a participatory method by involving MSME partners, which is accompanied by assistance during activities and evaluation of service activities. The results of the service activities show that Bu Sri's Gethuk MSMEs have received marketing training, bookkeeping training, and Good Manufacturing Process training, both in theory and hands-on practice. The success of this service activity can be seen in the use of social media and WhatsApp stories as a product marketing medium, the orderly and neat bookkeeping documents, and the arrangement of raw materials and finished products with a more systematic workflow. The results of the training have had a positive impact on Gethuk Bu Sri MSMEs because they can improve business management.